2011
DOI: 10.1108/02610151111110054
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination in health care industry: a research on public hospitals

Abstract: Purpose -The purpose of this study is to investigate discrimination areas within public hospitals and discuss the potential reasons that will provide a contributive perspective on reducing discriminative behaviors. Design/methodology/approach -The research was conducted in public hospitals in Afyonkarahisar, a city in the central-west part of Turkey. Two distinct approaches were used to gather data, one of which was a questionnaire that was responded by 351 health care employees. And, the second method semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Besides, Quite few studies about older employees in workforce has been carried out in Middle East [51][52][53][54]. In public hospitals, Jordan, according to Ababaneh, [51] older employees were more responsible, understand the job tasks and having more working experience than younger employees.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Quite few studies about older employees in workforce has been carried out in Middle East [51][52][53][54]. In public hospitals, Jordan, according to Ababaneh, [51] older employees were more responsible, understand the job tasks and having more working experience than younger employees.…”
Section: Methodsmentioning
confidence: 99%
“…They were protected from negative stereotypes and discriminations. It seems organizations favor the existence of older employees by instilling equal opportunities to all generations [52]. In Lebanon, according to Sidani et al [54] it was found that although older employees turn to be more ethical due to higher experience level, however, they were less comprehensive to recognize issues at different situations within organization.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Turkish healthcare system was characterized by its highly complex and fragmented provision and financing systems as well as inequalities in access to healthcare. In the year 2003, Turkey started Health Transition Program (HTP) to develop easily accessible, high-quality, efficient, and effective healthcare services for the population, which was also for the sake of pairing its healthcare system with the health regulations of the European Union (EU) and OECD countries [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such discrimination may be a result of status discrepancy between providers. 34 A fourth area was the challenge of maintaining physical distance and preventive protocols. The nature of the job and workplace routines for ODPs meant that they were unable to maintain physical distance from patients and co-workers.…”
Section: Discussionmentioning
confidence: 99%